EFFECT OF FERTILIZATION AND WATER STRESS ON STORAGE CHARACTERISTICS OF POTATO Solanum tuberosum L. - Z. A. Dawood (Mesopotamia Journal of Agriculture)
A field experiment was conducted at Al-Danadan potato farm in Mosul city during the spring season of 2000, to study the effects of two levels of k-fertilizer as KCl (0 and 20 kg. K/donum 2500m2) and four levels of NP fertilizer (0,50 kg. N donum+31.5 kg. P/donum, 75 kg.N/donum +47.25kg.P and 144kg.N/donum +47.25kg.P/donum), and the effects of water stress (normal irrigation and no water supply till plant reaches wilting during the period of tubers formation), on some storage characteristics of potato tubers. Results indicated that, K-fertilizer decreased significantly in the percentage of damage tubers (24.7%), and sprouting tubers 25% during the storage period, while espousing potato plants to water stress during the period of tuber formation resulted in a significant increases as 32.8 and 457.7% in both characteristics respectively under storage condition. Adding k-fertilizer and increasing levels of N/P fertilizer had a positive role to decrease the damage of water stress on storage characteristics of potato tubers.